Comparison of Conventional Polyethylene Wear and Signs of Cup Failure in Two Similar Total Hip Designs. (11th April 2013) - Pace, Thomas B.; Keith, Kevin C.; Alvarez, Estefania; Snider, Rebecca G.; Tanner, Stephanie L.; DesJardins, John D.
Abstract : Multiple factors have been identified as contributing to polyethylene wear and debris generation of the acetabular lining. Polyethylene wear is the primary limiting factor in the functional behavior and consequent longevity of a total hip arthroplasty (THA). This retrospective study reviewed the clinical and radiographic data of 77 consecutive THAs comparing in vivo polyethylene wear of two similar acetabular cup liners. Minimum follow-up was 7 years (range 7–15). The incidence of measurable wear in a group of machined liners sterilized with ethylene oxide and composed of GUR 1050 stock resin was significantly higher (61%) than the compression-molded, GUR 1020, O2 -free gamma irradiation sterilized group (24%)( P = 0.0004 ) . Clinically, at a 9-year average followup, both groups had comparable HHS scores and incidence of thigh or groin pain, though the machined group had an increased incidence of osteolysis and annual linear wear rate.